2023
DOI: 10.3390/jcm12103372
|View full text |Cite
|
Sign up to set email alerts
|

EGFR-Driven Mutation in Non-Small-Cell Lung Cancer (NSCLC) Influences the Features and Outcome of Brain Metastases

Abstract: Background: Brain metastases (BMs) is one of the most frequent metastatic sites for non-small-cell lung cancer (NSCLC). It is a matter of debate whether EGFR mutation in the primary tumor may be a marker for the disease course, prognosis, and diagnostic imaging of BMs, comparable to that described for primary brain tumors, such as glioblastoma (GB). This issue was investigated in the present research manuscript. Methods: We performed a retrospective study to identify the relevance of EGFR mutations and prognos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…7 ). 23 , 24 , 25 , 26 In this study, the natural histories of breast and lung cancer patients are consistent with those reported by others. 27 , 28 Still, under clinical, radiological and surgical aspects, there are some interesting differences especially regarding age, clinical debut, timing, extracranial metastases and surgical features.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…7 ). 23 , 24 , 25 , 26 In this study, the natural histories of breast and lung cancer patients are consistent with those reported by others. 27 , 28 Still, under clinical, radiological and surgical aspects, there are some interesting differences especially regarding age, clinical debut, timing, extracranial metastases and surgical features.…”
Section: Discussionsupporting
confidence: 92%
“…It is reported that the median survival of breast cancer patients with BM varies according to HER-2 subtype with the triple-negative forms having worse prognosis (about 6 months), than HER 2 positive HR (about 21 months). 56 In patients with metastasis from lung carcinoma, seems that the EGFR expression correlates with prognosis, 57 although our recent study 23 on this collection did not confirm this finding. Patients with metastasis from breast carcinoma present with more advanced intracranial disease than patients with metastasis from NSCLC but after treatment, no differences are reported between the two groups.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…For a high fraction of patients such molecular data is unknown at the time of evaluation for craniotomy. In addition, while the above mutations are associated with survival, the association is uncertain in patients with BM [ 38 , 39 ], and more studies are warranted to establish the role of oncogenic mutations in these patients. Further, studies have also shown discrepancies between mutation status in primary tumors and their BM [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The synchronous brain metastases, defined as the BM lesions occurring within 2 months of the primary cancer diagnosis and the prognosis is reported to be poor compared with metachronous lesions, which were defined as brain metastases found 2 months or more after the detection of the primary cancer [ 21 ]. A previous study suggested that the presence of EGFR mutations significantly correlates with greater edema and mostly a higher seizure incidence of BMs from NSCLC [ 22 ]. However, in clinical practice, patients diagnosed with treatment-naïve EGFR-mutant NSCLC without severe BM symptoms tend to choose EGFR-TKIs as first-line therapy and defer brain RT.…”
Section: Introductionmentioning
confidence: 99%